The problems of students knowledge in mathematics on entering LUA at 2000–2001 academic year - Kaminskienė, Janina; Raškinienė, Danutė (Lietuvos matematikos rinkinys, 2001)
This paper presents the results of the intemational test in mathematics at the beginning of 2000–2001 academic year at LUA. Comparison between results of different countries are done. Some conclusions are discussed here too.